SPIRITUAL DETERMINANTS AND SITUATIONAL CONTINGENCIES OF TRANSFORMATIONAL LEADERSHIP - F.V. Anthony; C.A.M. Hermans (Acta Theologica)
There is a strong evidence that transformational leadership gives rise to loftier motivation among the teaching staff, creative school innovation, enhanced learning results among students and critical openness to diversity in society. Little is known how school leaders can become better transformational leaders. Our research among school leaders of the Salesian schools in India seeks to verify if higher performance of transformational leadership is influenced by spiritual determinants (spiritual discernment, spiritual traits, spiritual capital, and spiritual experience), besides situational contingencies pertaining to personal profile and institutional features. The findings reveal that the prevalent leadership style in Salesian schools is transformational, and that it is strongly predicted by a combined spiritual trait of self-directed-cooperativeness and spiritual discernment, and moderately predicted by the situational contingencies of schools being private and having lesser student strength.